Facilitating Mental Health Literacy: Targeting Canadian First Nations Youth - Potvin-Boucher, Jacqueline T.; Malone, Judi L. (Canadian Journal of Counselling and Psychotherapy, 2014)
As reported rates of mental illness and suicide among Canadian First Nations youth continue to rise, counsellors are uniquely placed to contribute to mental health literacy. Development of contextually appropriate programs requires knowledge of the myriad of contributing factors including residual issues of colonization, discrimination, marginalization, and socioeconomic struggles that play pivotal roles in wellness and mental health risks. Given the potential contribution of such programs and the dearth of literature in this area, we reflect on what factors would contribute to facilitating or adapting existing mental health literacy programs to target Canadian First Nations youth. We explore ideas for integrating culture and context, youth engagement, and youth empowerment.